Performance Audit Of Multi-Year Road Infrastructure Project Implementation In The North Sumatra Provincial Government Fy 2023 - An Suci Azzahra (Pascasarjana STIE Amkop Makassar, 2025)
This study is a Performance Analysis Audit that aims to evaluate the effectiveness of the implementation of the Multi-Year Contract (MYC) Road Infrastructure Project in the North Sumatra Provincial Government (Pemprov Sumut) Fiscal Year (FY) 2023. This study was motivated by the importance of Performance Audits in realizing Public Accountability and the existence of material findings from the Supreme Audit Agency (BPK). The method used is descriptive qualitative analysis through in-depth documentation study (content analysis) of the BPK Audit Report on the North Sumatra Provincial Government's Financial Report for FY 2023. The results of the analysis show a collective failure to meet the 3E criteria (Effectiveness, Efficiency, Economy), as evidenced by potential deficiencies in the volume and quality of work, which resulted in overpayments amounting to IDR 138,867,590,370.33. This failure stems from weaknesses in the Contract Internal Control System (SPI) marked by inadequate approval of contract extension justifications and increased risk of fraud and overstatement of construction assets in progress (KDP). These findings also highlight the limitations of the effectiveness of APIP's functional oversight in preventing Contract Deviations. The study concludes that there is a need for systematic improvement of the Contract ICS and enhanced Audit Follow-up performance to ensure accountability in Capital Expenditure management, while reducing recurring audit findings in the future.Keywords: Performance Audit, Multi-Year Contract, Contract Deviation, Contract SPI, Public Accountability